Mepiquat chloride loss by simulated rain - Mateus, Gustavo Pavan (2004)
Brazilian cotton production is located in regions in which pluvial precipitation indexes are around 2,000 mm per year. Growth regulator application in conditions under such indices can make product to be washed before being absorbed by the plants. The objective of this research was to evaluate the effect of mepiquat chloride wash by simulated rain occurring at different times after the product application on cotton plants. The experiment was accomplished in greenhouse conditions, in pots of 12 L with three cotton plants cv. DeltaOpal. Mepiquat Chloride was sprayed at pin-head square, at 12.5 g ha-1 a.i. Treatments consisted on two simulated rainfalls intensity (10 and 20 mm) at 0, 2, 4, 8, 16 and 32 hours after the product application and a treatment without rain, with four replications. A 10 mm rain was enough to wash the product from cotton leaves irrespectively of the time after application of the regulator. If there is rain 0, 2, 4, 8, 16 or 32 hours after product application, it should be reapplied 131, 125, 120, 110, 93 and 70 mL ha-1, respectively